2012
DOI: 10.1007/s00228-012-1429-9
|View full text |Cite
|
Sign up to set email alerts
|

NAT2 genotype guided regimen reduces isoniazid-induced liver injury and early treatment failure in the 6-month four-drug standard treatment of tuberculosis: A randomized controlled trial for pharmacogenetics-based therapy

Abstract: ObjectiveThis study is a pharmacogenetic clinical trial designed to clarify whether the N-acetyltransferase 2 gene (NAT2) genotype-guided dosing of isoniazid improves the tolerability and efficacy of the 6-month four-drug standard regimen for newly diagnosed pulmonary tuberculosis.MethodsIn a multicenter, parallel, randomized, and controlled trial with a PROBE design, patients were assigned to either conventional standard treatment (STD-treatment: approx. 5 mg/kg of isoniazid for all) or NAT2 genotype-guided t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
196
0
12

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(217 citation statements)
references
References 25 publications
(28 reference statements)
9
196
0
12
Order By: Relevance
“…The adverse effect of ethambutol is mainly optic nerve damages, while liver injury is very rare. Pyrazinamide could cause arthralgia, appetite decrease, fever, and liver injury [12], as well as skin rash in some cases. Multi-center studies with large sample sizes in China have shown that [13] pyrazinamide in the HRZ strategy is a relatively high risk factor for liver injury, and the liver toxicity is dependent on the dose of pyrazinamide.…”
Section: Liver Function At Different Time Check Valuementioning
confidence: 99%
“…The adverse effect of ethambutol is mainly optic nerve damages, while liver injury is very rare. Pyrazinamide could cause arthralgia, appetite decrease, fever, and liver injury [12], as well as skin rash in some cases. Multi-center studies with large sample sizes in China have shown that [13] pyrazinamide in the HRZ strategy is a relatively high risk factor for liver injury, and the liver toxicity is dependent on the dose of pyrazinamide.…”
Section: Liver Function At Different Time Check Valuementioning
confidence: 99%
“…En Japón ya se han empezado ensayos clínicos para evaluar el cambio de régimen de tratamiento basado en los polimorfismos del gen NAT2 (37) , Azuma et al, se basaron en estudios previos de farmacocinética para determinar la dosis clínica apropiada para cada genotipo. De acuerdo con estos estudios, individuos con fenotipo lento deben recibir mitad de la dosis estándar, mientras que individuos con fenotipo rápidos deben recibir 1,5 veces la dosis estándar (38) .…”
Section: Terapia Basada En La Farmacogenómicaunclassified
“…Inadequate exposure to TB drugs constitutes one of the main factors underlying suboptimal treatment response and development of resistance, as evidenced by results from: the in vitro hollow fibre model [1]; clinical studies on relationships between drug concentrations and response [2-5]; a pharmacogenetic trial [6]; and a recent meta-analysis [7].More specifically, these concentration-effect evaluations suggest that clinicians should prescribe higher doses of rifampicin [2,5], that acetylator status should be used to determine the dose of isoniazid [6,7], and that higher doses and exposures to pyrazinamide may increase efficacy [4,5].Clearly, such studies also underline the relevance of careful concentration-effect evaluations during the development of new TB drugs that will eventually be applied by clinicians all over the world.Finally, these studies support the concept of therapeutic drug monitoring (TDM) of TB drugs as applied by clinicians and pharmacists in selected centres around the world [8][9][10]. In contrast to administering the same fixed dose to all patients, TDM seeks to individualise drug doses, guided by measurement of serum (or plasma) drug concentrations.…”
mentioning
confidence: 99%
“…Inadequate exposure to TB drugs constitutes one of the main factors underlying suboptimal treatment response and development of resistance, as evidenced by results from: the in vitro hollow fibre model [1]; clinical studies on relationships between drug concentrations and response [2-5]; a pharmacogenetic trial [6]; and a recent meta-analysis [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation